Institute of Coding in Wales Digital Skills Bootcamps – Micro-Credentials: A Pilot Project - Casey Hopkins (Proceedings of the 8th Conference on Computing Education Practice, 2024)
From October 2021 to July 2022, the Institute of Coding (IoC) in Wales carried out a pilot project, delivering digital skills bootcamps across every university in Wales. The project aimed to test the universities’ appetite and ability to implement mechanisms awarding university credits to those undertaking these bootcamps; so-called micro-credentials. As a result of this project, 349 learners were recruited onto 16 bootcamps. Six of these bootcamps saw the learners obtain university credits; the remaining ten bootcamps were non-credit-bearing which nonetheless provided essential upskilling opportunities. This paper reflects on the outcomes of this project, discussing the challenges faced, delivery mechanisms used, learner demographics, completion rates, and future ambitions.